Pemberdayaan Desa dengan Keunikan Kemasan Produk pada “One Village One Product” di Kecamatan Bontomarannu - Geraldina, Ira; Arifin, Andi Harmoko; Rahim, Abdul Rahman; Andriyansah, Andriyansah (Civiliza Publishing, 2024)
Although faced with various problems, MSMEs in Indonesia have increased every year, in 2021 MSMEs numbered 63, 955, 369 units and in 2022 the number reached 8.71 million units. The partners of this activity are fostered MSMEs in three villages, namely Romang Lompoa, Balang-Balang, and Borongloe Villages, Bontomarannu District, Gowa Regency. The urgency of this activity is to minimise difficulties in marketing, intense business competition The solution given to overcome partner problems is to improve the quality of product packaging for fostered partners and increase sales of fostered partner products. The solution given to overcome partner problems is to improve the quality of product packaging of fostered partners and increase sales of fostered partner products.